Adventures in Odyssey. Vol. 22, The changing times [compact disc]. - Leigh, Katie; Madden, Dave, 1931-2014; Ryan, Will (Performer) (Adventures in Odyssey audio series, 1995)
Odyssey seems full of change these days as Tom Riley runs for mayor, George Barclay and his family discover the difficulties of preparing for the ministry, Jason Whittaker arrives amidst international intrigue and Jack uncovers a strange code book in Whit's workshop.